1999
DOI: 10.1093/ajcn/69.6.1249
|View full text |Cite
|
Sign up to set email alerts
|

School-administered weekly iron-folate supplements improve hemoglobin and ferritin concentrations in Malaysian adolescent girls

Abstract: Long-term, weekly iron-folate supplementation was found to be a practical, safe, effective, and inexpensive method for improving iron nutrition in adolescent schoolgirls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
1
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 5 publications
4
59
1
3
Order By: Relevance
“…Repeating the analysis among only those children who were dewormed or among only those not dewormed showed similar results as the analysis done for the two groups combined. Furthermore, the improvement in Hb concentration after the implementation of the school-based WISDS is consistent with the improvement in the Hb concentration in other school-based weekly iron supplementation studies that had a control group, in particular among schoolchildren in Mali (Hall et al, 2002) and among adolescent schoolgirls in Malaysia (Tee et al, 1999) and in Mozambique (Horjus et al, 2005).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Repeating the analysis among only those children who were dewormed or among only those not dewormed showed similar results as the analysis done for the two groups combined. Furthermore, the improvement in Hb concentration after the implementation of the school-based WISDS is consistent with the improvement in the Hb concentration in other school-based weekly iron supplementation studies that had a control group, in particular among schoolchildren in Mali (Hall et al, 2002) and among adolescent schoolgirls in Malaysia (Tee et al, 1999) and in Mozambique (Horjus et al, 2005).…”
Section: Discussionsupporting
confidence: 85%
“…Compliance has been reported to be influenced by the undesirable side effects brought about by iron tablet intake, which are related to the amount, frequency and duration of intake, and form of the tablets (Charoenlarp et al, 1988;Aguayo et al, 2005). Side effect is dose related as seen in studies conducted among Malaysian adolescent girls (Tee et al, 1999) and Bangladeshi pregnant women (Hyder et al, 2002). The 60 mg dose seems to have had no adverse effects among schoolchildren in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Similar high compliance under programme conditions similar to our study was reported by Kotecha et al (5) in 2002 among rural and tribal adolescent girls of Gujarat. Like other authors (6,7) we used school teachers as supervisors for IFA supplementation as they can positively influence their students for compliance better than anybody else. Additionally, we used anganwadi workers as supervisors only to those adolescent girls who were not going to school and we also used standardized methods of compliance checking, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Three months of daily supplementation with 1 mg folic acid and multivitamin during the postpartum period produced slight, though signi®cant, increases in mean Hb and Hct levels (2 g l -1 and and 0.008, respectively) compared to multivitamin use alone among lactating American women 77 . However, no bene®t of folic acid supplementation on Hb response was observed in trials among either non-pregnant Thai women 67 or Malaysian adolescent girls 78 . In the latter study, however, plasma ferritin increased signi®cantly following supplementation with iron and folate, but decreased in the folate-alone group, suggesting that folate may have stimulated synthesis of Hb from existing iron stores.…”
Section: Folatementioning
confidence: 96%